Ocular syphilis in patients with human immunodeficiency virus/acquired immunodeficiency syndrome in the era of highly active antiretroviral therapy - Sridharan Sudharshan; Nitin K Menia; Poongulali Selvamuthu; Mudit Tyagi; N Kumarasamy; Jyotirmay Biswas (Indian Journal of Ophthalmology, 2020)
Purpose: Re-emergent ocular syphilis in patients with Human immunodeficiency virus (HIV) co-infection has both diagnostic and management difficulties because of the overlapping risk factors. The clinical manifestations described in non-HIV may not be the same in patients with HIV coinfection. Immune recovery uveitis (IRU) may also alter the course of the disease causing recurrences. We studied the clinical features in correlation with CD4 counts, systemic immune status, sexual preferences and management outcomes in HIV/AIDS patients with ocular syphilis in the highly active antiretroviral treatment (HAART) era from a high endemic HIV population like India. Methods: Retrospective analysis of all patients with ocular syphilis and HIV/AIDS seen between 2016 and 2019 was done. Results: A total of 33 patients (56 eyes) with a CD4 count range of 42–612 cells/cu.mm were included. Ocular syphilis was found to be higher in individuals with high risk behavior such as men who have sex with men (MSMs) (45%). Panuveitis was the commonest manifestation (53.57%) and was even the presenting feature of HIV and syphilis in many patients. Significant vitritis, usually uncommon in HIV/AIDS immunocompromised patients was noted even with low CD4 counts in patients with ocular syphilis. Significant correlation was noted between ocular presentation and CD4 counts (P < 0.05). Conclusion: Ocular syphilis presents differently in patients with HIV/AIDS. Diffuse retinitis is seen commonly in low counts (<100 cells/cu.mm). Classical placoid chorioretinitis lesions usually described in non-HIV individuals is uncommon in HIV patients and is seen in higher CD4 counts ( >400 cells/cu.mm). Ocular manifestations can be an indicator of the immune status of the patient. Not all patients with ocular manifestations have associated features of systemic syphilis. Ocular manifestations can be the first presentation of HIV/AIDS. Although, there is good response to systemic penicillin and HAART, recurrences and immune recovery uveitis (IRU) can also occur.